Comparing the effects of team-based and problem-based learning strategies in medical education: a systematic review - Weilin Zhang; Jinsong Wei; Weixiong Guo; Zhongwei Wang; Siyuan Chen (BMC Medical Education, 2024)
Abstract Background Recently, there has been a concerted effort within medical schools to depart from conventional lecture-based learning approaches to alternative teaching methods such as team-based learning (TBL) and problem-based learning (PBL), with the aim of enhancing both student engagement and instructional efficacy. Despite this shift, a comprehensive review that directly compares the impacts of PBL and TBL methods in medical education is lacking. This study seeks to address this gap by conducting a meta-analysis that compares the effects of TBL and PBL in the context of medical education. Methods Studies from Embase, PubMed, Web of Science, China National Knowledge Infrastructure, and Chinese Wanfang Database were searched, from inception to July 11, 2023. A meta-analysis was performed using Stata 14.0, and a total of 10 studies (including 752 participants) were included. The standardized mean difference (SMD) was used to estimate pooled effects. Heterogeneity was detected using the I2 statistic and further explored using meta-regression analysis. Results Compared with PBL, TBL significantly increased the number of theoretical tests (SMD = 0.37, 95% CI: 0.02–0.73). Additionally, TBL greatly improved teamwork skills compared with PBL. However, there were no significant differences between the TBL and PBL groups concerning practical skill scores, learning interest, or understanding skills. Conclusion TBL in the theoretical aspects of medical education appears to be more effective than PBL in improving theoretical test scores and teamwork skills, providing evidence for the implementation of TBL in medical education.